Neurotensin agonist PD 149163 modulates the neuroinflammation induced by bacterial endotoxin lipopolysaccharide in mice model. (4th March 2022) - Mishra, Ankit; Singh, K. P.
Abstract: Objective: The disruption of bidirectional communication between neuroendocrine and immune components by stressors leads to mental problems. The immunomodulation therapy of neuroinflammation-led psychiatric illness is an emerging area of research. Therefore, the present study aimed to evaluate immune modulation efficacy of PD 149163 (PD) against the lipopolysaccharide (LPS)-induced neuroinflammation. Materials and methods: The Swiss albino mice (female/12 weeks) were divided into six groups (6 mice/group): (I) Control: 0.9% NaCl; (II) LPS: 1 mg/kg BW, for 5 days; (III) LPS + PD Low: LPS 1 mg/kg BW (for 5 days) after that PD 100 µg/kg BW (for 21 days); (IV) LPS + PD High: LPS 1 mg/kg BW (for 5 days) after that PD 300 µg/kg BW (for 21 days); (V) PD Low: PD 100 µg/kg BW (for 21 days); (VI) PD High: PD 300 µg/kg BW (for 21 days). All treatments were given intraperitoneal. Results: The LPS-induced weight loss (body and brain) was normalized to control after PD treatment. The PD enhanced superoxide dismutase (SOD) activity while decreased lipid hydroperoxide (LOOH) level altered in LPS-exposed mice. The significantly increased pro-inflammatory cytokines (IL-6 and TNF-α) in LPS exposure were also decreased by PD. Likewise, the LPS-induced HPA axis activation was stabilized by PD. In the hippocampus, the pyramidal cell layer thickness, pyramidal neurons number and size of CA1 and CA3 regions were reduced along with misalignment, shrinkage, and impairment of cytoarchitecture. In the co-treated group, the LPS-induced hippocampus disruption was reversed after PD exposure. Conclusion: We suggested that the PD modulates the LPS-induced neuroinflammation and psychiatric illness in a dose-dependent manner.